What of It? Coding the Unmarked Of-Preposition in Language Samples from Young AAE Speakers - Finneran, Denise A.; Moyle, Maura J.; Nash, Alaina; Chen, Sixia (Seminars in Speech and Language, 2025)
We examined the of-preposition in language samples because it is a highly variable feature that can be marked or unmarked (e.g., “out [of] the door”) depending on context. Children who speak African American English (AAE) produce unmarked of-prepositions in contexts that are universal across AAE and General American English (GAE; e.g., “out [of] the window”) and in contexts specific to the AAE dialect (e.g., “out [of] the car”). Guidance in the literature on this variability is limited for language sample analysis. Participants included 113 children who spoke AAE. We examined contexts with unmarked of-prepositions in narrative language samples in a subset of 72 children (mean age = 53.57 months). Samples were coded for AAE features based on the published literature. Contexts with an unmarked of-preposition were coded as universal (present in AAE and GAE) or as a feature of AAE. We calculated an estimate of AAE feature use in two ways: one that erroneously assumed that all of-preposition variability (including universal) is AAE, and one that more precisely identified AAE features. Analyses revealed significant differences in the measurement of AAE use. Careful analysis of dialect-specific and universal features of AAE grammar, including the of-preposition, is needed for reliable assessments.
Keywords: African American English; preposition; narrative; language sample analysis; child language